2002
DOI: 10.1002/ijc.10669
|View full text |Cite
|
Sign up to set email alerts
|

Human papillomavirus type 16 is episomal and a high viral load may be correlated to better prognosis in tonsillar cancer

Abstract: The aim of our study was to investigate the physical state and the viral load of HPV-16 in tonsillar cancer and to correlate these findings with clinical outcome. To distinguish between integrated and episomal forms of HPV, 22 freshfrozen tonsillar cancer samples were analysed by a method based on restriction enzyme cleavage, ligation and PCR (rliPCR). HPV-16 was detected in 11/22 and HPV-33 in 1/22 of the cancers, hence 12/22 (55%) of the tumours were HPV positive. Only extrachromosomal forms of HPV-16 were o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

15
209
6
6

Year Published

2005
2005
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 204 publications
(236 citation statements)
references
References 28 publications
(57 reference statements)
15
209
6
6
Order By: Relevance
“…Other strong indicators for a favorable prognosis in our study include tumor diameter o4 cm, low/no expression of cyclin D1, and low/no tobacco consumption. In accordance with most other studies on HPV-related oropharyngeal carcinomas, we also found a favorable disease-specific survival in patients with HPV16-positive tonsillar squamous cell carcinomas, 12,46,[60][61][62][63][64] and p14 ARF overexpression, 31 although with less significance than the indicators described above. We noticed that lymph node status, which is generally considered as the most important prognostic factor in head-and-neck squamous cell carcinomas, 23 had little value in our series of tonsillar squamous cell carcinomas, which is in concordance with other studies.…”
Section: Discussionsupporting
confidence: 92%
“…Other strong indicators for a favorable prognosis in our study include tumor diameter o4 cm, low/no expression of cyclin D1, and low/no tobacco consumption. In accordance with most other studies on HPV-related oropharyngeal carcinomas, we also found a favorable disease-specific survival in patients with HPV16-positive tonsillar squamous cell carcinomas, 12,46,[60][61][62][63][64] and p14 ARF overexpression, 31 although with less significance than the indicators described above. We noticed that lymph node status, which is generally considered as the most important prognostic factor in head-and-neck squamous cell carcinomas, 23 had little value in our series of tonsillar squamous cell carcinomas, which is in concordance with other studies.…”
Section: Discussionsupporting
confidence: 92%
“…27 Most of these studies employed the gold-standard for HPV viral load assessment: real-time PCR. 27,28 However, based on this study, it seems that the less costly, more feasible semiquantitative method may also have utility in epidemiologic studies in which laborious real-time PCR assays may not be possible. Important limitations may exist for both semiquantitative and quantitative viral load assessment.…”
Section: Discussionmentioning
confidence: 91%
“…The HPV copy numbers found in HNSCCs are often lower than detected in cervical cancers. Among HNSCC, the highest copy numbers are detected in palatine tonsillar cancers and the best survival figures are reported to those tonsillar cancers harboring the highest copy numbers and episomal form of HPV [52]. As discussed earlier, not all HPV genomes are replicating in the cells.…”
Section: Hpv and Head And Neck Cancer (Hnscc)mentioning
confidence: 90%
“…The HPV types have also been grouped into mucosal or cutaneous types, based on their tropism for specific epithelial sites. Mucosal HPV types found preferentially in precancerous and cancerous lesions have been designated as 'high-risk' types and these include types 16,18,31,33,34,35,39,45,51,52,56,58,59, 66, 68, and 70. Mucosal HPVs found in benign genital warts and other non-malignant lesions are generally labeled as 'low-risk' types, the most important ones being HPV 6,11,42,43, and 44 [1,2].…”
Section: Human Papillomaviruses (Structure and Classification)mentioning
confidence: 99%